Factors Encouraging Athletes’ Interest in Joining the SMAPA Volleyball Clu (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2026)
This study aims to analyze the factors encouraging athletes’ interest in joining the SMAPA Volleyball Club and to identify the most dominant factors influencing their participation. Volleyball clubs play an important role in athlete development, not only in improving technical skills and performance but also in shaping motivation, discipline, and social interaction among athletes. However, athletes’ interest in joining sports clubs is influenced by various internal and external factors that require deeper investigation. This study employed a qualitative descriptive approach involving athletes, coaches, and club administrators at the SMAPA Volleyball Club, SMAN 1 Parang, Magetan. Data were collected through open-ended questionnaires, in-depth interviews, observation, and documentation using purposive sampling techniques. Data analysis was conducted through data reduction, data display, and conclusion drawing, while triangulation techniques were applied to ensure data validity and reliability. The findings indicate that athletes’ interest is influenced by both internal and external factors. Internal factors include interest and hobby in volleyball, achievement motivation, self-confidence, self-development, and perceived physical and mental benefits. Meanwhile, external factors consist of parental support, peer influence, the role of coaches, training facilities, club achievements, and opportunities to participate in competitions. Interest and hobby (90%) as well as achievement motivation (88%) emerged as the most dominant internal factors, while parental support (89%) and club achievements (87%) were identified as the strongest external influences. In conclusion, athletes’ participation is shaped through the interaction between psychological motivation and environmental support systems. Therefore, sports clubs should optimize both personal and social factors to sustain athlete involvement and improve sports development programs.